Increasing Human Resource Capacity in The Development of Limbungan Traditional Villages and Perigi Villages, East Lombok District - Ferdianto, Jujuk; Hizmi, Surayyal; Supardi, Supardi; Wahim, Isdar; Syahrihudin, Syahrihudin; Darsa, Lalu Hari; Juanda, Juanda (Sumber Belajar Sejahtera, 2024)
Limbungan Traditional Village is located in Perigi Village with traditional potential that can be introduced as one of the tourist attractions in the village. Apart from that, there are many potential tourist attractions whose potential the people in Perigi village have not yet realized. The main obstacle in this village is the absence of special human resources focused on developing and managing the area as a tourist attraction, even though the East Lombok Regency government has designated Perigi village, especially the Limbungan Traditional Village, for tourism development. Therefore, the Lombok Poltekpar Service Team designed a human resource development program consisting of preparation stages, baseline study, coordination, coaching and mentoring, monitoring and evaluation. Based on the activities carried out, there are around 25 active young people who have been formed to develop Perigi village and Limbungan Traditional Village as tourist attractions. The provisions that have been obtained from increasing human resource capacity include the ability to prepare tour packages, story telling and basic services to guests. It is hoped that this activity to increase human resource capacity can be the first step for the village government and community to develop their village into a tourist attraction and provide awareness or sustainable benefits in the tourism sector.